Mortality and morbidity in early preterm breech singletons: impact of a policy of planned vaginal delivery. (September 2015) - Kayem, Gilles; Combaud, Vanessa; Lorthe, Elsa; Haddad, Bassam; Descamps, Philippe; Marpeau, Loic; Goffinet, Francois; Sentilhes, Loic
Abstract: Objective: To compare neonatal morbidity and mortality rates in preterm singleton breech deliveries from 26 0/7 to 29 6/7 weeks of gestation in centers with a policy of either planned vaginal delivery (PVD) or planned cesarean delivery (PCD). Study design: Women with preterm singleton breech deliveries occurring after preterm labor or preterm premature rupture of membranes (pPROM) were identified from the databases of five perinatal centers and classified as PVD or PCD according to the center's management policy. The independent association between planned mode of delivery and the risk of neonatal hospital death or morbidity was tested and quantified with ORs through two-level multivariable logistic regression modeling. Results: Of 142 782 deliveries during the study period, 626 (0.4%) were singletons in breech presentation from 26 0/7 to 29 6/7 weeks of gestation: after exclusions, 130 were in the PVD group and 173 in the PCD group. Severe newborn morbidity was similar in the two groups. Newborn mortality was 12% in the PCD group and 16% in the PVD group. Three neonates (1.7%, 95% CI: 0.34–5.0) died from head entrapment after vaginal delivery in the PVD group. Nonetheless, the policy of PVD was not associated with increased risks of neonatal death (aOR: 1.01, 95% CI: 0.33–2.92) or severe morbidity. Conclusion: Risks of mortality and severe morbidity in preterm breech were not increased by a policy of vaginal delivery. Head entrapment leading to death is however possible in cases of vaginal delivery but its rarity should be balanced with the maternal consequences of early preterm cesarean delivery.